PENGARUH PENGUNGKAPAN ENVIRONMENTAL, SOCIAL, GOVERNANCE (ESG) TERHADAP KINERJA PERUSAHAAN (Studi Empiris pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Tahun 2016-2021) - Hilmy Muhammad Hartomo; Agustinus Santosa Adiwibowo (Diponegoro Journal of Accounting, 2023)
In carrying out its business activities, companies are required to not only pay attention to profits, but also must pay attention to the impact arising from the course of the company's operational activities. One of the efforts to overcome this is to pay attention to environmental, social, and corporate governance factors. This study aims to analyze the impact of Environmental, Social, and Governance (ESG) disclosures on company performance. The disclosure of ESG scores used is a combination of three factors, namely environmental, social, and corporate governance. The company's performance measurement is carried out using Return on Asset (ROA), Return on Equity (ROE), and Tobin's Q. This study also uses control variables, including Asset Turnover (AG) and Asset Growth (AG).The sample used in this study is manufacturing companies in Indonesia, namely 26 manufacturing companies that have revealed Environmental, Social, and Governance scores in 2016 – 2021 using the purposive sampling method with secondary data obtained from the Bloomberg database. This study used multiple linear regression analysis panel data and used IBM SPSS Statistics 25 software.The findings of this study illustrate that ESG score variables have a positive influence on company performance which in this study uses Return on Asset (ROA), Return on Equity (ROE), and Tobin's Q proxies.